A Program to Increase Cure Rate of Tuberculosis in Namyuen Hospital, Ubon Ratchathani Province - Promsuree, Phakaidao (Journal of Health Science of Thailand, 2017)
Tuberculosis is a national problem that requires active case finding and complete treatment with expected national cure rate of over 90%. Namyuen Hospital has been taking care of the population in Namyuen and Namkhun districts with 99,970 population; and has regularly seen patients with tuberculosis. The problems frequently faced by the hospital included higher dead rate than the national average, limited empowerment of patients, irregular follow-ups, irregularity and self-termination of treatment, difficulty in coordination between the hospital and the communities which did not pay attention to the importance of the TB situation. Such problems had let to the failure to achieve target cure rate of which the rate for 2008 to 2010 was 75.0, 50.0 and 71.2 percent respectively. The objective of this study was to improve the cure rate of TB to achieve over 90 percent by applying empowerment theory to develop successful and sustainable treatment system which integrated 3 sets essential components – clients, care team and community into the 3C=empowerment model. The approach was utilized for the treatment of all 210 TB cases in 2011-2013; and the cure rate was raised to 96.7, 100.0 and 100.0 percent respectively. Other indicators were also improved which included zero loss to follow-up, zero default rate and zero death. The 3C=empowerment model was shown to improve the treatment of tuberculosis; and application of the model for other chronic diseases was recommended.